Nasopharyngeal carriage of otitis media pathogens in infants receiving 10-valent non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV10), 13-valent pneumococcal conjugate vaccine (PCV13) or a mixed primary schedule of both vaccines: A randomised controlled trial. Issue 16 (15th April 2021) - Beissbarth, J.; Wilson, N.; Arrowsmith, B.; Binks, M.J.; Oguoma, V.M.; Lawrence, K.; Llewellyn, A.; Mulholland, E.K.; Santosham, M.; Morris, P.S.; Smith-Vaughan, H.C.; Cheng, A.C.; et al.
Abstract: Background: Aboriginal children in Northern Australia have a high burden of otitis media, driven by early and persistent nasopharyngeal carriage of otopathogens, including non-typeable Haemophilus influenzae (NTHi) and Streptococcus pneumoniae (Spn). In this context, does a combined mixed primary series of Synflorix and Prevenar13 provide better protection against nasopharyngeal carriage of NTHi and Spn serotypes 3, 6A and 19A than either vaccine alone? Methods: Aboriginal infants (n = 425) were randomised to receive Synflorix™ (S, PHiD-CV10) or Prevenar13™ (P, PCV13) at 2, 4 and 6 months (_SSS or _PPP, respectively), or a 4-dose early mixed primary series of PHiD-CV10 at 1, 2 and 4 months and PCV13 at 6 months of age (SSSP). Nasopharyngeal swabs were collected at 1, 2, 4, 6 and 7 months of age. Swabs of ear discharge were collected from tympanic membrane perforations. Findings: At the primary endpoint at 7 months of age, the proportion of nasopharyngeal (Np) swabs positive for PCV13-only serotypes 3, 6A, or 19A was 0%, 0.8%, and 1.5% in the _PPP, _SSS, and SSSP groups respectively, and NTHi 55%, 52%, and 52% respectively, and no statistically significant vaccine group differences in other otopathogens at any age. The most common serotypes (in order) were 16F, 11A, 10A, 7B, 15A, 6C, 35B, 23B, 13, and 15B, accounting for 65% of carriage. Ear discharge swabs (n = 108) were culture positive for NTHi (52%), S. aureus (32%), and pneumococcus (20%). Conclusions: Aboriginal infants experience nasopharyngeal colonisation and tympanic membrane perforations associated with NTHi, non-PCV13 pneumococcal serotypes and S. aureus in the first months of life. Nasopharyngeal carriage of pneumococcus or NTHi was not significantly reduced in the early 4-dose combined SSSP group compared to standard _PPP or _SSS schedules at any time point. Current pneumococcal conjugate vaccine formulations do not offer protection from early onset NTHi and pneumococcal colonisation in this high-risk population.